SCHOOL-ENVIRONMENT AND ITS EFFECTS ON THE ACADEMIC ACHIEVEMENT ON GIRLS IN SECONDARY EDUCATION: A CASE OF KISUMU EAST SUB- COUNTY, KENYA - S.A. L., Juma; R.O., Luchivya (African Journal of Education and Practice, 2018)
Purpose: The purpose of this study was to find out the influence of school environment on girls' academic achievement at Secondary School Education level in Kisumu East Sub- County. Methodology: The research designs used were correlation and descriptive survey designs. The study population consisted of 1560 girls from form four, 39 head teachers and 39 class teachers. Simple random sampling technique was used to select 300 form four girls. Saturated sampling technique was used to select 30 head teachers and 30 class teachers. Data collection instruments included questionnaire, interview schedule and document analysis guide. Findings:The study established that school environment affected girls' academic achievement. Unique contribution to theory, practice and policy: The recommendations of the study were; Schools should advice parents on how to properly use their resources on supporting their daughters' academic performance other than making negative comments. The study may be significant to education policy makers, planners and implementers on how to provide secondary education that will enhance girls' academic achievement. Keywords: Factors, education, school environment, girls' academic achievement, Kisumu East Sub- County.